Dynamics of banking sector integration in South Asia: an empirical study. Issue 3 (11th November 2019) - Pandey, Piyush; Sehgal, Sanjay; Ahmad, Wasim
Abstract : Purpose: Banks in the South Asian region are the fulcrum of economic growth and development as they provide means to development credit and working capital, trade and infrastructure finance and are seen as custodians of the trust in the financial system. This paper aims to study the nature of banking sector linkages for the region. Design/methodology/approach: The dependence structure between deposits and lending rates individually for the banks of the South Asian countries are studied using time invariant and time varying family of copula functions. The degree of connectedness is further studied by Diebold and Yilmaz methodology. Findings: Results indicate poor levels of banking integration in the region as the dependence parameter for both deposits and lending rates was around 0 for the sample countries, thereby confirming poor banking sector integration in the region. Practical implications: Policymakers of the region are interested in the co-movements of the interest rates to understand the cross-sector risk management and any systemic risk pressures for the regional economies. Corporates in these countries are scouting out for competitive borrowing rates to lower their cost of capital. Social implications: Rationale for examining the banking sector linkages is that the South Asian countries are at different stages of economic growth and development and this region in particular is the fastest growing region in the world and has largely increased its trade integration with the world albeit having lowest levels of intra-regional trade integration. Originality/value: This is a first of a kind of studies to examine the banking sector linkages in South Asia.